2021
DOI: 10.1177/1043454221992306
|View full text |Cite
|
Sign up to set email alerts
|

Parent Caregiving Experiences and Posttraumatic Growth Following Pediatric Hematopoietic Stem Cell Transplant

Abstract: Background: Parents of children recovering from hematopoietic stem cell transplant (HSCT) experience significant distress due to unpredictable and potentially life-threatening complications. Distress is heightened by intensive caregiving parents provide the child during the first 100 days after HSCT. Management of distress and adaptation to caregiving responsibilities may be enhanced if parents find benefit in their experiences through posttraumatic growth (PTG), yet little is known about how parents’ experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…10 Turning to similarities between pediatric transplant and oncology, both areas have utilized qualitative interviewing methods to understand PTG in a depth not afforded by self-report questionnaires. 21,22,25,26,33,34 This review highlights important gaps in the literature and future directions to investigate. First, it is important to note that this review aimed to include studies that also examined PTG among siblings of pediatric transplant recipients, but no such studies were identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Turning to similarities between pediatric transplant and oncology, both areas have utilized qualitative interviewing methods to understand PTG in a depth not afforded by self-report questionnaires. 21,22,25,26,33,34 This review highlights important gaps in the literature and future directions to investigate. First, it is important to note that this review aimed to include studies that also examined PTG among siblings of pediatric transplant recipients, but no such studies were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the studies conducted qualitative interviews of children and parents or caregivers utilizing various methodologies. 21,22,25,26 One of the studies interviewed adolescent SOT recepients 21 while two interviewed parents of SCT recipients, 22,26 and one interviewed mothers of kidney transplant recipients only. 25 The study that interviewed adolescents 21 highlighted three consistent areas of PTG that emerged including personal, relationship, and introspective growth.…”
Section: Qualitative Studies Of Youth and Caregiversmentioning
confidence: 99%
“…The PTG process has been investigated among people with chronic diseases, such as CC, however studies mainly examine the survivors (12)(13)(14)(15) and the caregivers (16)(17)(18) separately. Some studies approached CC survivors and their caregivers together, but most of them did not investigate the cognitive processes (e.g., challenge to core beliefs and rumination) involved in the PTG (3,19) .…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as social support, support from healthcare professionals, and counseling are considered to be highly correlated with post-traumatic growth in individuals who have undergone BMT (Jeon et al, 2015). A study found evidence of post-traumatic growth in caregiver parents of transplanted adolescents and found that care-related responsibilities contribute to this positive outcome (Beckmann et al, 2021).…”
mentioning
confidence: 99%
“…These findings suggest the need to implement interventions that encourage the development of adaptive resources and optimize coping, encouraging autonomy and minimizing the toxic effects of chronic exposure to stress (Oliveira-Cardoso et al, 2018). Work with parents should focus on actions focused on positively reinterpreting their children's post-BMT experiences (Beckmann et al, 2021).…”
mentioning
confidence: 99%